2022
DOI: 10.1038/s41598-022-15590-z
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress mitigation in tomato (Solanum lycopersicum L.) through foliar application of gibberellic acid

Abstract: Phytohormones mediate physiological, morphological, and enzymatic responses and are important regulators of plant growth and development at different stages. Even though temperature is one of the most important abiotic stressors for plant development and production, a spike in the temperature may have disastrous repercussions for crop performance. Physiology and growth of two tomato genotypes ('Ahmar' and 'Roma') were studied in two growth chambers (25 and 45 °C) when gibberellic acid (GA3) was applied exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…At the end of the 3rd month, the plants in soil + electrohydrogenesis effluent generated more fruit with big size than the control plants (see Fig. 8 ), but the tomato ( Solanum lycopersicum L.) didn’t generate fruits in both protocols at that time probably due to the high weather temperature that inhibitory affected its continuous growth, as previously reported that tomato species are generally so sensitive to temperature change 28 , 29 . The final yield was evaluated in terms of the size and number of fruits per cultivated plant.…”
Section: Resultssupporting
confidence: 50%
“…At the end of the 3rd month, the plants in soil + electrohydrogenesis effluent generated more fruit with big size than the control plants (see Fig. 8 ), but the tomato ( Solanum lycopersicum L.) didn’t generate fruits in both protocols at that time probably due to the high weather temperature that inhibitory affected its continuous growth, as previously reported that tomato species are generally so sensitive to temperature change 28 , 29 . The final yield was evaluated in terms of the size and number of fruits per cultivated plant.…”
Section: Resultssupporting
confidence: 50%
“…Salicylic acid and Jasmonic acid, hormones which are known for the biotic stress hormones also play a role in abiotic stress tolerance. In wheat application of SA and JA has shown to increase the germination during the drought stress [52]. Even exogenous application of SA helps in salt stress response in cucumbers [53] and reports have shown their role in heavy metal toxicity tolerance too [54].…”
Section: Plant Stress Responses and Defense Mechanismsmentioning
confidence: 99%
“…Increasing MDA content and electrolyte leakage due to heat stress were observed in several plants. Tomato leaves of thermosensitive and thermotolerant genotypes exposed to heat stress showed elevated MDA content and electrolyte leakage [ 27 ]. Electrolyte leakage of Indian mustards increased in both thermotolerant and thermosensitive genotypes ranging from 2–2.75-fold after heat stress treatment, compared to the control, while MDA content was notably higher in thermosensitive genotypes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%